Fire and drought: Shifts in bark investment across a broad geographical scale for Neotropical savanna trees - Scalon, Marina Corrêa; Rossatto, Davi Rodrigo; Oliveras, Imma; Miatto, Raquel Carolina; Gray, Emma Fiona; Domingos, Fabricius Maia Chaves Bicalho; Brum, Fernanda Thiesen; Carlucci, Marcos Bergmann; Hoffmann, William Arthur; Marimon-Júnior, Ben Hur; Marimon, Beatriz S.; Franco, Augusto Cesar (Basic and applied ecology, 2021)
•Inner bark thickness at the community level vary across a continental-size biome range.•There was little variation in outer bark for branches and main stem.•Higher water deficit was associated with higher inner bark thickness•Bark trait composition of species in core region were nested within peripheral regions Savanna tree communities occurring in confluence zones with other biomes likely experience different environmental pressures, resulting in shifts in the selection of individual traits, the combinations of such traits, and species composition. In seasonally dry fire-prone environments, plant survival is presumably associated with adaptive changes in bark properties related to fire protection and water storage. Here, we integrated the multiple functions of the bark to investigate whether different selective pressures could influence patterns of variation in bark structure and allocation across species in a broad geographical range. We measured thickness, density, and water content of the inner and outer bark in branches and the main stem of the 51 most abundant species in three savanna communities differing in climatic aridity, one located at the core region of Cerrado in Central Brazil and the other two at its periphery, in the transition zones with Amazonia and Atlantic forest biomes. We found no difference in outer bark thickness but markedly difference in inner bark thickness between the three plant communities. In the central region, where dry season is long and fire is frequent, branches and main stem showed thicker inner bark. Contrastingly, in the south periphery region, where dry season is short, species showed thinner inner bark in both branches and main stem. Species from the north periphery region, where mean annual precipitation is higher, but fire is frequent and the dry season is also long, showed similar main stem inner bark thickness, but thinner branch inner bark compared to core region species. Our findings support the idea that investing in inner bark thickness and bark moisture may be the most advantageous strategy in plant communities that suffer from high evaporative demand during a long period and are at a high risk of fire.